IMPROVING THE QUALITY OF VOCATIONAL EDUCATION ON THE BASISOF SUSTAINABLE DEVELOPMENT (Innovative professional education, 2024)
Modern software tools, as well as methods of working with a report posted on the Internet, make it possible to solve pedagogical tasks in a new way, which contributes to theformation of students’ skills to work independently with information flows, to analyze various non-standard situations. Their use significantly supports traditional cognitively oriented education, since computerization and technological education significantly expand the intellectual activity of future specialists.
Keywords: digital education, digitalization, gamerization, information technologies, environmentalization